Primary stability of short stem prostheses for the shoulder: a biomechanical comparative study of two short stem designs - Nolte, Anna-Katharina; Seifert, Maxime Marie; Jäger, Sebastian; Kretzer, Jan Philippe; Schonhoff, Mareike; Zeifang, Felix; Trefzer, Raphael; Panzram, Benjamin; Renkawitz, Tobias; Bülhoff, Matthias (Archives of orthopaedic and trauma surgery, 2025)
The use of short stems has been a trend in shoulder arthroplasty within the last 15 years with excellent short- to mid-term clinical outcomes. Short stems anchor in the cancellous metaphysis and a high level of postoperative stability with absence of micro-movements at the bone-implant interface can be crucial for the following healing. The study aimed to assess the primary rotational stability of two uncemented short stems. The hypothesis was that the rotational stability is independent of implant design.
Online veröffentlicht: 20. August 2025
Gesehen am 17.12.2025